Belajar Menyanyikan Tembang Macapat sebagai Upaya Pelestarian Budaya dan Peningkatan Kemampuan Bahasa Daerah di Sekolah Dasar Negeri - Ayu Ekawati, Nadia; Subrata, Heru (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
This study aims to describe the process of teaching tembang macapat singing in elementary school as a strategy for cultural preservation and strengthening regional language competence. Using a participatory qualitative approach, the research was conducted at UPT SD Negeri 195 Gresik during the first semester of the 2025/2026 academic year. Subjects were selected purposively, involving regional language teachers and fifth-grade students. Data were collected through participatory observation, semi-structured interviews (July 26, 2025), and photo documentation. The findings indicate that actively singing tembang macapat improves students' mastery of chromo alus and chromo inggil vocabulary while instilling character values such as simplicity, responsibility, and cultural pride. Teachers contextualized song meanings to make them more relatable. Some students sang the songs at home and taught them to siblings, indicating cultural transfer beyond school. Despite limited learning media, teachers applied contextual strategies. Overall, this learning approach proved effective, enjoyable, and meaningful for elementary students.